Short review of the forest insect pest in Argentina - Fiorentino, D. C.; Diodato de Medina, L. (Forest Systems, 1991)
A chronological analysis of the Argentinian insect pests affecting not only native but introduced tree species as well, is presented. The main pests were arranged in accordance with their economical consequences and allocated by taking into consideration their taxonomy (Order, Family and Species). The insect geographical distribution, host species and damages are also described. The families included are: Formicidae, Cerambicidae; Curculionidae, Platipodidae, Chrysomelidae, Tortricidae, Psichidae, Hemileucidae, Megalopygidae, Phycitidae, Pyralididae, Aphididae, Adelgidae and Cercopidae.